Romania : Technical Assistance Report on Reforming Personal Income Taxation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
With one of the lowest revenues in the EU and a projected budget deficit exceeding 7 percent of GDP, Romania should rely on an array of tax (policy and administration) instruments to mobilize revenues. A fundamental question facing Romania's reform efforts is how to spread the burden of the tax in an equitable manner, especially given the already relatively high income inequality. The fiscal system as a whole currently provides little income support at the bottom of the income distribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Romania